Melnick-Needles syndrome associated molecule, Filamin-A regulates dental epithelial cell migration and root formation. Issue 3 (December 2020) - Hino, Ryoko; Yamada, Aya; Chiba, Yuta; Yoshizaki, Keigo; Fukumoto, Emiko; Iwamoto, Tsutomu; Maruya, Yuriko; Otsu, Keishi; Harada, Hidemistu; Saito, Kan; Fukumoto, Satoshi
Abstract: Background: Filamin-A (FLNA) is one of the adaptor proteins binding to both integrin beta chain and actin filament. Several kind of mutation in human FLNA gene were observed in Melnick-Needles syndrome (MNS). However, the role of FLNA in tooth formation is still unknown. Matrials and methods: We analyzed the tissue expression of FLNA during tooth development using immunostaining. The role of FLNA in cell migration was analyzed using a scratch assay. In addition, we analyzed the phenotype of teeth in patients with Mernick-Needles syndrome caused by FLNA gene abnormalities. Results: FLNA expressed in inner and outer enamel epithelium in mouse tooth germ and also expressed in cervical region of dental epithelium. In postnatal stage, FLNA expressed in ameloblast and odontoblast layers. In rat dental epithelium cell line SF2, FLNA is localized at the boundary between cells and co-localized with the terminal region of F-actin filament. shRNA-FLNA transfected cells showed delayed cell migration and scratch closure compared with control cells. Analysis of actin fiber movement by time-lapse confocal microscopy showed slower fiber movement in shRNA-FLNA over expressing SF2 cells. Novel mutation in FLNA gene was observed in MNS with tooth anormaly. This patient showed tooth agenesis and short root in both primary and permanent dentition with thin enamel. Conclusion: Taken together, these results suggest that filamin-A is play a key role for dental epithelium migration and root formation.